Les parlers acadiens : un continuum discontinu - Neumann-Holzschuh, Ingrid; Wiesmath, Raphaële (Canadian Journal of Applied Linguistics, 2006)
We adopt the hypothesis that the varieties of Acadian French, geographically distant from one another in North America for quite some time, constitute an interlinguistic continuum based on the structural space which separates them. Furthermore, all varieties of Acadian French show a high degree of internal variability. Based on an analysis of the restructuring of a number of grammatical sub-systems (conditional clauses, non-finite verb forms) and of a number of discontinuities concerning the presence or absence of certain features typical of Acadian French, we conclude that the variational space of Acadian French is a complex example of continuities and discontinuities to which the scalar model can only partially be applied.